The Role of Halaqoh Tarbawiyah in the Formation of Adolescents' Self-Concept at Muhammadiyah 10 Middle School Surakarta - Asmara, Linda; Shobahiya, Mahasri; Sodikin, Aditya Wisnu (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2025)
This study aims to examine the role of halaqoh tarbawiyah in shaping the self concept of adolescents at SMP Muhammadiyah 10 Surakarta, Indonesia. Adolescence is a critical phase in identity development, where cultivating a strong self concept is essential. Halaqoh tarbawiyah, a group-based Islamic educational approach, is expected to serve as a medium for nurturing Islamic character in adolescents. This research employed a descriptive qualitative approach using a case study method. Data were collected through in-depth interviews, observations, and documentation involving students, teachers, and halaqoh tarbawiyah facilitators. The findings indicate that halaqoh tarbawiyah plays a significant role in developing adolescents’ self concept through three main aspects: the internalization of Islamic values, the enhancement of self-confidence, and the cultivation of social awareness. Moreover, the halaqoh serves as a safe and supportive space for adolescents to share experiences, participate in discussions, and explore their identities. Therefore, the implementation of halaqoh tarbawiyah in Islamic schools functions as a strategic instrument for strengthening Islamic identity and addressing identity crises during adolescence.